2012
DOI: 10.1039/c1sm06589k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels with well-defined peptide-hydrogel spacing and concentration: impact on epithelial cell behavior

Abstract: The spacing of peptides away from a hydrogel matrix dramatically impacts their availability and subsequent interactions with cells. Peptides were synthesized with monodisperse poly(ethylene glycol) spacers of different lengths that separate the peptide from the monomeric functionality which reacts during hydrogel polymerization. Specifically, bioactive RGD ligands were conjugated to PEG5, PEG11 or PEG27 spacers via solid phase techniques and then functionalized with an acryloyl end group. These acryloyl-PEGx-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
0
34
1
Order By: Relevance
“…The hydrogel precursor solution consists of a nonfouling PEG polymer and peptides, where both components were functionalized with acrylate groups. 6 In the presence of a photoinitiator and UV source, the hydrogel precursor components were copolymerized, creating a cross-linked hydrogel network that retained the nanoscale ridge and groove pattern of the stamp. The hydrogel arrays were hydrated and allowed to swell prior to cell culture, which resulted in an approximate 30% increase in the hydrogel volume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrogel precursor solution consists of a nonfouling PEG polymer and peptides, where both components were functionalized with acrylate groups. 6 In the presence of a photoinitiator and UV source, the hydrogel precursor components were copolymerized, creating a cross-linked hydrogel network that retained the nanoscale ridge and groove pattern of the stamp. The hydrogel arrays were hydrated and allowed to swell prior to cell culture, which resulted in an approximate 30% increase in the hydrogel volume.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that the conjugation of peptides to pure, monodisperse PEG spacers and subsequent acrylate functionalization allows peptides to be incorporated via radical polymerization at high efficiencies, with high reproducibility. 6 The peptides are covalently bound via an amide bond to eliminate concerns of hydrolysis of the peptide for longterm studies that usually accompany peptide incorporation schemes like Michael-type addition. 5 The hydrolytic cleavage of the PEGDA ester bonds between the aliphatic polymer backbone and the crosslinking unit has been shown by other groups to be limited during the time frame of our experiments, and the swelling ratio has been shown to not significantly change over the course of 6 weeks (where complete degradation is estimated to be on the order of months to years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation of cellular behavior and differentiation by soluble factors, 15,[36][37][38][39] surface chemistry, [40][41][42][43][44] and biophysical attributes of the extracellular microenvironment [45][46][47][48] has been well established. While, the majority of studies have investigated only one type of biophysical or chemical cue in isolation, a limited number have explored the interaction between multiple biophysical cues, 11,49 surface chemistry, 19,50 or soluble cytoactive factors. 15 Here we have demonstrated that the simultaneous presentation of substratum topographic cues and surfaceassociated biochemical cues potently modulated cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pep1Alloc concentration may be adjusted for different applications (e.g., 0.2-5 mM) as reported in literature for thiol-functionalized peptides. [18][19][20][21] LAP concentration is recommended around 0.067 wt% (2.2 mM) or less, as described, as higher concentrations can decrease cell viability. 4.…”
Section: Introductionmentioning
confidence: 99%